2003
DOI: 10.1001/archpedi.157.7.687
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Functional Status, Family Stressors, and Psychosocial Adjustment Among School-aged Children With Disabilities in the United States

Abstract: Children's functional activity limitations and family stressors are significant correlates of psychosocial adjustment among children with disabilities. These data indicate a need for routine screening for mental health problems among children with disabilities, as well as a family-oriented approach to their medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(60 citation statements)
references
References 67 publications
4
52
0
4
Order By: Relevance
“…Two studies based on the National Health Interview Survey were considered, but discarded. One of these [Witt et al, 2003] mixed current depressive symptoms with those occurring in the past year, making it …”
Section: Selection Of Articles For Study Inclusionmentioning
confidence: 99%
“…Two studies based on the National Health Interview Survey were considered, but discarded. One of these [Witt et al, 2003] mixed current depressive symptoms with those occurring in the past year, making it …”
Section: Selection Of Articles For Study Inclusionmentioning
confidence: 99%
“…7 Among youth with various disabilities, parental functioning has been found to predict child adjustment. 8,9 A group investigating posttraumatic stress disorder (PTSD) among youth with SCI and their caregivers found that mothers' PTSD predicted patients' and fathers' PTSD, and that patient's PTSD predicted mothers' PTSD. 10 Among youth with limb deficiencies, poor parental mental health predicted child's mental health; however, this relationship was statistically eliminated when taking into account children's perceived social support.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] For examp le, whi le Ne wacheck et al 18 and Pa ul et al 11 fo und di sa bi lity to be mo re pre va lent among chil dren of fa mi li es with inco mes be low the po verty le vel, Mcdo u gall et al 8 re por ted that chil dren who se fa mi li es we re re ce iving wel fa re in co me we re mo re li kely to ha ve chro nic he alth and ac ti vity-li mi ting con di ti ons than tho se not re ce i ving wel fa re in co me. Ho gan et al 10 and Witt et al 30 re por ted that func ti o nal li mita ti ons we re mo re clo sely as so ci a ted with fa mily eco logy. In our study, the ra te of ac ti vity-li mi ta tions was hig her in boys than in girls, and in the 13-17 age gro up than in the 7-12.…”
Section: Discussionmentioning
confidence: 74%